Internalisasi Nilai-Nilai Pendidikan Islam dalam Membentuk Karakter Santri Melalui Pembelajaran Tahfizul-Quran di Rumah Tahfiz Quran Muslimin Medan - Muhammad Luthfie Ramadhani; Imron Bima Saputra; Nursyahrul Ritonga; Roslaeni Roslaeni; Indra Syah Putra (Education Achievement: Journal of Science and Research, 2026)
This research aims to analyze the process of internalizing Islamic educational values ​​through Quran memorization learning, the formation of student character through the internalization of Islamic educational values ​​in Quran memorization learning, supporting and inhibiting factors in the internalization of Islamic educational values ​​to shape student character through Quran memorization learning at the Muslimin Quran Memorization House in Medan. This research is a qualitative research. Using data collection techniques in the form of observation, interviews and document studies. For data analysis used in this study, the Miles and Huberman model was used with data validity using source triangulation. Based on the research results, it can be concluded that the internalization of Islamic educational values ​​through learning Tahfiz Al-Qur'an at Rumah Tahfiz Quran Muslimin Medan is carried out systematically through teacher role models, habituation of worship, fostering manners, and religious culture integrated into the learning process. This process has succeeded in forming the Qur'anic character of students which is reflected in religious attitudes, discipline, honesty, responsibility, independence, and noble character. The success of internalization is supported by teacher role models, a religious learning environment, and parental support, while differences in student character, lack of family support, the influence of digital media, and limited facilities and time are inhibiting factors. Therefore, synergy between the tahfiz house, family, and the environment is an important factor in optimizing the formation of student character through learning Tahfiz Al-Qur'an.